Implementasi Manajemen Waktu Dalam Inovasi Pembelajaran Online Pada Mata Pelajaran PAI - Munfiatik, Siti; Mubarok, Ramdanil (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2023)
The problem of time management during this pandemic has become a hot topic of discussion and needs to be researched. This research will try to analyze how effective time management is, how time management is implemented in online learning, and what the obstacles are to implementing time management in online learning. The method applied in this research is descriptive-qualitative. Data was taken and collected through observation and interview techniques. The data were analyzed using Miles & Huberman's interactive model analysis. The result is that managing time effectively requires a priority scale plan (planning), making schedules and deadlines (organizing), commitment to implementation (actuating), and making improvements (evaluation). Implementation of time management in online learning innovation can be done by determining learning objectives, arranging material priority scales, preparing meeting schedules, being assertive in the learning process, being firm, not delaying time, and controlling the time you have. Forms of innovation that can be carried out in controlling study time at home are collaboration with students' parents and direct control by teachers via social media platforms. Obstacles to implementing time management in online learning innovations include technical obstacles related to technology and internet networks, limited facilities and infrastructure, not being on time, and student commitment.